Pendekatan Tafsir Produk Perbankan Syariah - Abdul Mujib (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2015)
As a financial intermediary institution, Islamic banks offer several products in the form of funding, financing, and other services. The product as regulated in Law No. 21 of 2008 concerning Islamic Bank. Products, as mentioned above, refer to the results of the Fatwa issued by National Shariah Council of MUI. Fatwa is commonly used in the implementation of funding and financing namely DSN-MUI No. 1/DSNMUI/IV/2000 about Giro, DSN-MUI No. 2/DSN-MUI/IV/2000 about Saving, DSN-MUI No. 3/DSN-MUI/IV/2000 about Deposit, dan DSN-MUI No. 7/DSN-MUI/IV/2000 about Mudharabah Financing.